FOOD HABITS AND FEEDING HABITS OF BARRAMUNDI FISH (Lates calcarifer Block) IN TERUSAN DALAM (INSIDE CANAL) WATERS, EAST COAST OF SOUTH SUMATERA PROVINCE - Ridho, Mohammad Rasyid; Patriono, Enggar (BIOVALENTIA: Biological Research Journal, 2016)
Research about the food habits and feeding habits of Barramundi (Lates calcarifer Block) in Terusan Dalam (inside canal) waters, East coast of South Sumatera Province, had been done during March to June 2012. The purpose of this research was to analyze the food habits and feeding habits of Â Barramundi (Lates calcarifer Block) on Terusan Dalam (inside canal) waters, East coast of South Sumatera Province. Sampling method of the fish was purposive sampling method using Tangsi net. The results of this research showed that the number of fish from March to June totaled 31 individuals of fish. Based on the Relative Importance Index (RII), the natural food of Barramundi (Lates calcarifer Block) in March to June 2012 consisted of shrimp as the main food with the Relative Importance Index 72.37-99.51%, the fish was as the complement food with the Relative Importance Index 11.33-27.63%, and as the additional food was the worm with Relative Importance Index 0.49%.Keywords: Barramundi, food habits, feeding habits